Reading Test Construction - B. Budiyono; B. Himawan Setyo Wibowo (Widya Mandala Surabaya Catholic University, 2012)
The importance of reading skills accounts for a number of credits to reading courses. It also accounts for a variety of formats of assessment such as weekly assessment and end-of-term tests. For that reason, Barrett’s taxonomy proposes itself to be a reference for reading test construction. It suggests operational skills to be tested.